Diagnostic ability of pancreatic juice cytology via the minor papilla in patients with pancreas divisum. Issue 1 (28th September 2021) - Kawaguchi, Shinya; Satoh, Tatsunori; Terada, Shuzo; Endo, Shinya; Shirane, Naofumi
Abstract: Background and study aim: Endoscopic retrograde cholangiopancreatography (ERCP) is generally performed via the major papilla when evaluating patients with pancreatic disease. However, in patients with pancreas divisum (PD) or distortion of the main pancreatic duct, endoscopic retrograde pancreatography (ERP) should be performed via the minor papilla (MP). Our aim was to evaluate the efficacy and safety of endoscopic pancreatic juice cytology (PJC), performed via the MP, in patients with PD. Patients and methods: Patients with PD who underwent diagnostic ERP via the MP, between January 2010 and February 2021, were identified retrospectively from our hospital's ERCP database. Twenty‐two patients contributing to 24 ERCPs were included in the analysis. Results: MP cannulation was successful in 23 of 24 ERCPs (96%). In one patient, successful cannulation was achieved on the second attempt and the procedure was performed twice in another. Serial pancreatic juice aspiration cytologic examination (SPACE) was performed in 17 patients, with a single aspiration of pancreatic juice performed in the other five. The sensitivity, specificity, and accuracy rates of ERCP diagnosis, overall, were 56%, 100%, and 80%, respectively. When diagnosis only based on SPACE was considered, the accuracy rate was even higher at 87%. Three patients (13%) developed mild pancreatitis as an adverse event. Conclusions: The diagnostic ability of endoscopic PJC, via the MP in patients with PD was technically feasible and relatively effective under experienced pancreatobiliary endoscopists, however, requiring careful attention to post‐ERCP pancreatitis when performed.